The study of value representations of a sociocultural community construction considering the interdisciplinary interaction of history and empirical sociology - Khlebnikov, I.D. (KSU Publ., 2020)
This article is concerned with the issues of interdisciplinary interaction of history and empirical sociology as related to the study of value representations of a socio-cultural community construction. The authors focus on fixing historical trends in the formation of the socio-cultural community of Kazakhstan at the micro level. Sociocultural community refers to representatives of one society who identify themselves with it and are endowed with a number of similar historically determined cultural characteristics, norms and values that distinguish them from representatives of other societies. Regarding Kazakhstan, we are talking about the influence of the historical experience of different generations, including the Soviet and earlier periods, which have influenced the processes of the socio-cultural community developing at the present stage, since they are still part of the identity of a significant number of representatives of Kazakh society. Based on the research, the authors conclude that age and ethno-cultural factors have significant impact on the effectiveness of the historical transformation of spiritual and moral values leading to formation of Kazakhstan's identity and the success of the construction of Kazakhstan's socio-cultural community which is determined by different strategies of socialization, language practice and historical experience of the respondents.
Тарих пен эмпирикалық əлеуметтанудың пəнаралық өзара əрекеттестігі аясында əлеуметтік-мəдени қауымдастық құрудың құндылықты репрезентацияларын зерттеу
Изучение ценностных репрезентаций построения социокультурной общности в свете междисциплинарного взаимодействия истории и эмпирической социологии
Keywords: sociocultural community; polyethnicity; modern history of Kazakhstan; oral history; identity; interdisciplinary interaction; specific historical problems; questionnaire survey